HIV patients, healthy aging and transplant recipients can reveal the hidden footprints of CMV. - Waters, Shelley; Brook, Emily; Lee, Silvia; Estiasari, R.; Ariyanto, I.; Price, Patricia (Academic Press, 2018)
Cytomegalovirus (CMV) is a β-herpesvirus. Latent infections are common in all populations. However age-associated increases in levels of CMV-reactive antibody are testament to repeated reactivations and periods of viral replication. CMV has been associated with several diseases of aging, including vasculopathy and neurocognitive impairment. These conditions occur at a younger age in persons with particularly high burdens of CMV - transplant recipients and people living with HIV. Here we define the “clinical footprints” as immunopathologies triggered by CMV that develop over many years. A high burden of CMV also drives accumulation of multifunctional terminally-differentiated αβ T-cells, a novel population of Vδ2 − γδ T-cells, and a population of CD56lo NK cells lacking a key regulatory molecule. An understanding of these “immunological footprints” of CMV may reveal how they collectively promote the “clinical footprints” of the virus. This is explored here in transplant recipients, HIV patients and healthy aging.